Mapping Flood Co-Adaptation Strategies in a Vulnerable River Basin: Engaging Youth in Collaborative Decision-Making - Zulfaqar Sa’adi; Zainura Zainon Noor; Nur Syamimi Zaidi; Ee Ling Yong; Fateha Abdul Razak; Nurul Hana Mohamed; Zainab Mat Lazim; Ainul Syarmimi Rosli; Mohd Faiz Foze; Siti Hanna Elias; Khairunnisa Abdul Halim; Muhammad Burhanuddin Bahrodin; et al. (Environmental Management, 2026)

AI-Enabled Digitalization and Environmental Practices in Municipal Waste Management: Pathways to Climate Sustainability in Pakistan - Muhammad Ahsan Iqbal; Asifa Muhammad Sabir; Kundan Kumar; Md Mahfujul Islam (Environmental Management, 2026)
Rapid urbanization and the intensifying pressures of climate change have elevated solid waste management (SWM) as a critical public service challenge. Evidence on the joint mediating effects of digital transformation and environmental governance between municipal SWM and climate sustainability remains questionable. This study examines the role of SWM in promoting climate sustainability by evaluating environmental management practices and AI-enabled digitalization. Data were collected from 406 employees across seven Water and Sanitation Service Companies (WSSCs) in Khyber Pakhtunkhwa, Pakistan, using a cross-sectional survey with a structured and validated instrument. The analytical approach involved Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with bootstrapped mediation analysis (5000 resamples), executed in SPSS and AMOS software. The study measured waste management effectiveness, environmental practices, AI-enabled digital systems, and sustainability outcomes across economic–environmental–social nexus. Findings reveal a significant positive relationship between effective SWM and climate sustainability (β = 0.41, p < 0.001). Environmental practices including regulatory compliance, pollution control, and workforce training along with AI-driven digital capabilities including real-time tracking, route optimization, electronic service reporting, and data dashboards play a strong mediating role (indirect effects: ENV = 0.13; DIG = 0.12; joint = 0.21). The results suggest that municipal waste systems achieve greater climate benefits when routine operations are supported by integrated environmental management and smart digital technologies. The study contributes to the research on sustainable models, circular economy, and smart urban governance, offering policy guidance for municipal authorities in Pakistan, through AI-enabled tools and solutions, environmental governance practices, and SDG-aligned incentives.

Spatial Distribution and Risk Assessment of Heavy Metal Pollution at an Abandoned Smelting Site in Guangxi Province of China - Bodong Xiong; Lizhu Hou; Wajahat Waseem; Weihua Cui; Muhammad Asad ghafoor (Environmental Management, 2026)

Wetland Transformation and Waterfowl Decline: Linking Habitat Change to Northern Pintail Losses in Punjab - Nayyar Batool; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Misbah Sarwar; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Shaheen Riaz; Hakim Bibi (Environmental Management, 2026)

Understanding encroachment typologies through remote sensing and socio-economic analysis: enhancing national park management in Kerinci Seblat National Park, Indonesia - Muhammad Habib; Dedy Fitriawan; Kazuhiro Harada (Environmental Management, 2025)
Encroachment remains a persistent challenge for Kerinci Seblat National Park (KSNP), despite its designation as a protected area. While agricultural use by local communities continues, limited understanding of the actors and their motivations hampers effective policy responses. This study addresses this gap by integrating remote sensing with socio-economic analysis to examine encroacher typologies and their spatial dynamics. Land use and land cover (LULC) changes were detected using Landsat 5, 7, and 8 imagery across six time periods (1988–2022), analyzed through maximum likelihood classification. Field surveys were conducted with 206 households, alongside in-depth interviews with customary leaders, village heads, and KSNP. We found an increasing trend of encroachment since the initial identification of the KSNP to the present, which correlates with the expansion of agricultural land. We grouped the typologies of encroachers into indigenous landless (23%), indigenous people with economic opportunities (29%), sly opportunists (2%), indigenous people as investors (3%), workers/profit-sharing partners (42%), and local migrants (1%). The dominant typology was workers/profit-sharing partners, which indicates that this partnership has a broad influence and wide coverage. Grouping actors supports the implementation of programs according to their motives and characteristics. The solution to encroachment should include a livelihood improvement program for indigenous people without land ownership, the establishment of utilization (e.g., agroforestry areas) and buffer zones, and enhanced law enforcement for other typologies.

Gender Perspectives in Environmental Initiatives across Developing Countries - Ilyas Ahmad; Muhammad Usman; Shahbaz Imran; Wang Yue (Environmental Management, 2025)

Climate Change Policy Coherence across Policies, Plans, and Strategies in Pakistan—Implications for the China–Pakistan Economic Corridor Plan - Abdul Waheed; Thomas Bernward Fischer; Muhammad Irfan Khan (Environmental Management, 2021)
Climate Change (CC) adaptation and mitigation policy coherence (PC) across sectors is essential to effectively address CC challenges and support synergies. Pakistan is highly vulnerable to CC. In this paper, the extent to which Pakistan’s national and provincial water, agriculture, and energy sector policies, development plans and strategies are aligned in a CC policy coherent manner is established. In this context, a qualitative content document analysis with associated scoring is used to assess government documents. Furthermore, implications of the China–Pakistan Economic Corridor Initiative (CPEC; 2017–2030), the biggest infrastructure investment program ever in Pakistan, are discussed. An important result is that sectoral policies are found to have different degrees of PC. Better coherence is found at federal than at provincial levels. Furthermore, CC policies are found to be more coherently addressed in water and agriculture policies than in energy policies. It is suggested that to achieve higher levels of CC PC, federal and provincial governments should establish mechanisms of intergovernmental consultation for policy-making and cross-sectoral planning, especially in the energy sector. Our findings can help the Government of Pakistan to transform CPEC into a model green Belt and Road Initiative (BRI) in the region. In this context, there are important implications with regards to e.g., reducing coal-based energy projects and environmentally damaging infrastructure activities in sensitive ecosystems. With this paper, the authors want to raise awareness of the key importance of CC PC, particular in context of the BRI. Many countries participating in the initiative have carbon reduction targets in place.

Farmer Perceptions of Climate Change, Observed Trends and Adaptation of Agriculture in Pakistan - Muhammad Abid; Jürgen Scheffran; Uwe A. Schneider; Ehsan Elahi (Environmental Management, 2019)

Toxicological Assessment and UV/TiO2-Based Induced Degradation Profile of Reactive Black 5 Dye - Muhammad Bilal; Tahir Rasheed; Hafiz M. N. Iqbal; Hongbo Hu; Wei Wang; Xuehong Zhang (Environmental Management, 2018)

The Influence of Agroforestry and Other Land-Use Types on the Persistence of a Sumatran Tiger (Panthera tigris sumatrae) Population: An Individual-Based Model Approach - Muhammad Ali Imron; Sven Herzog; Uta Berger (Environmental Management, 2011)

Genotypic Variation in the Phytoremediation Potential of Indian Mustard for Chromium - Hema Diwan; Altaf Ahmad; Muhammad Iqbal (Environmental Management, 2008)